2001
DOI: 10.1292/jvms.63.111
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Babesia Species from Infected Dog Blood by Polymerase Chain Reaction.

Abstract: ABSTRACT. Polymerase chain reaction (PCR) was first applied to diagnosis of canine babesiosis in Japan. Blood samples from 13 dogs suffering from canine babesiosis were used for examination of specificity and sensitivity of the PCR diagnosis. Of the 13 dogs, three were experimentally infected, and ten were naturally infected with Babesia species in west part of Japan. We designed a nested PCR to amplify the babesial small subunit ribosomal RNA gene and found that only the nested PCR produced a visual band, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…PCR has also been shown to be more sensitive than microscopic-based diagnosis of Babesia spp. (Almeria et al 2001;Ano et al 2001). However, for identification of the parasite species, molecular methods should be combined with light microscopy (Valkiūnas et al 2008).…”
Section: Microscopic Analysesmentioning
confidence: 99%
“…PCR has also been shown to be more sensitive than microscopic-based diagnosis of Babesia spp. (Almeria et al 2001;Ano et al 2001). However, for identification of the parasite species, molecular methods should be combined with light microscopy (Valkiūnas et al 2008).…”
Section: Microscopic Analysesmentioning
confidence: 99%
“…Leishmaniasis was diagnosed by enzyme-linked immunosorbent assay (ELISA) in serum and confirmed by polymerase chain reaction (PCR) in whole blood. Furthermore, differential diagnosis with infections that cause the same kidney lesions in our working area, such as ehrlichiosis and babesiosis, was performed using ELISA [1,24] and PCR [2,13]. The same protocol as that used on leishmaniasis infected dogs was applied to the control group dogs to confirm the absence of this, or any other disease that could affect the results of this study.…”
Section: Animalsmentioning
confidence: 99%
“…Infections of dogs with Babesia piroplasms have been documented all around the world (Ano et al, 2001;Schaarschmidt et al, 2006). Brown et al (2006) investigated 215 isolates of Australian dogs' blood.…”
Section: Babesiosis -Occurrence and The Clinical Picturementioning
confidence: 99%
“…The authors emphasized that in the diagnostics of babesiosis, the determination of the species, subspecies and even genotype that caused the babesiosis in dogs is very essential, because virulence, prognosis and response to medicines against Babesia may be different in every organism. Ano et al (2001) tested the sensitivity of the nested PCR protocol carried out on the basis of the gene fragment encoding 18S rRNA in dogs experimentally infected and in naturally infected patients. They found that visualization of the product after the first-round of PCR was poor in both groups and that only after the second round was there a clear band on the agarose gel.…”
Section: Molecular Diagnostics: Selection Of a Genetic Marker For Pcrmentioning
confidence: 99%